A Fe(III)-g-C3N4 catalytic material and its preparation method and application

By preparing Fe(Ⅲ)-g-C3N4 catalytic material and permanganate to synergistically activate persulfate, the problem of easy failure of the activator and accumulation of iron sludge in the existing technology is solved, and efficient organic pollutant degradation is achieved.

CN118237063BActive Publication Date: 2025-01-24GUANGZHOU HAINONGCHUANG AGRI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410372251.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-01-24
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

In the existing advanced persulfate oxidation technology, the activator is prone to failure, high environmental conditions requirements and secondary pollution of iron sludge is generated, the electroactivation technology is complex in operation, high in cost and low system efficiency.

Method used

Use Fe (Ⅲ) -g-C3N4 catalytic material. By mixing the anterior anterior driver with melamine, burning and grinding for centrifugal washing, prepare the G-C3N4 catalyst with load FE (Ⅲ) Sulfate is used to degrade organic pollutants.

Benefits of technology

It achieves efficient oxidation catalytic degradation effect, avoids activator failure and iron sludge accumulation problems, reduces operational complexity and cost, and improves system efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118237063B_ABST
    Figure CN118237063B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of catalytic material preparation and relates to a Fe(III)-g-C 3 N 4 Catalytic material and its preparation method and application. The catalytic material includes a carrier g-C 3 N 4 and a loading substance Fe(Ⅲ), which is prepared by grinding and mixing an iron precursor and melamine, calcining, grinding, and then centrifuging and washing. 3 N 4 The raw materials of catalytic materials are abundant, cheap, and easy to produce. The Fe(Ⅲ) activator is not easy to fail and will not cause iron sludge accumulation. 3 N 4 / Mn(VII) activated PMS system can effectively remove organic dyes or difficult-to-degrade organic matter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalytic material preparation, and more specifically relates to a Fe(III)-g-C3N4 catalytic material and a preparation method and application thereof. Background Art

[0002] In recent years, water pollution caused by recalcitrant organic pollutants (ROPs) has become a serious problem faced by mankind. ROPs are widely present in wastewater from chemical, printing and dyeing, pharmaceutical, papermaking and other industries. They generally include polycyclic aromatic hydrocarbons, halogenated hydrocarbons, heterocyclic compounds, organic cyanides, organophosphorus pesticides, surfactants, organic dyes and other organic substances. These substances have the characteristics of long-term residual, bioaccumulation, semi-volatility and high toxicity. Many toxic recalcitrant organic substances cannot be removed by conventional treatment methods. Therefore, it is of great significance to develop economical and effective ROPs control and treatment technologies.

[0003] The attention paid to advanced oxidation processes (AOPs) based on peroxymonosulfate (PMS) in removing organic pollutants from water continues to increase. Advanced oxidation process (AOP) is considered to be an effective method for degrading ROPs through redox reactions. Among them, sulfate-based AOP (SR-AOP) process can produce sulfate radicals (SO4 ·- ) and hydroxyl radicals (HO·), which can quickly and efficiently degrade ROPs, and thus have attracted widespread attention. However, if persulfate is not activated, the removal effect is far less effective than the effect of degrading pollutants in the form of free radicals after activation. Therefore, the selection of persulfate activators and their properties will play a crucial role in pollutant degradation. Among the many activation methods, the transition metal activation method does not require complex preparation of the reaction system and is economical. Among the available activating metal ions, iron is widely used to catalyze the degradation of various pollutants by persulfate because it has no toxic effects, is abundant in source, is cheap, and is easy to produce. A variety of iron-based catalysts (such as Fe 2+ , Fe2O3, and Fe3O4) are widely used in the activation process of PMS due to their high environmental friendliness and cost-effectiveness. However, in a homogeneous system, dissolved iron ions can react freely with persulfate, which will lead to some limitations in the activation reaction, such as activator failure and iron sludge accumulation. Therefore, current research at home and abroad is increasingly inclined to load transition metal ions on nanomaterials. g-C3N4 (graphite-like carbon nitride) is an excellent loading material due to its non-toxic and low-density advantages.

[0004] Permanganate (Mn(VII)) is a relatively common oxidant with selective oxidation ability for certain organic pollutants. Compared with other chemical oxidants, Mn(VII) has a high reduction potential and is attractive because of its relative stability, ease of handling, relatively low cost, and the absence of chlorinated or brominated byproducts. In addition, the reduction products of Mn(VII) are environmentally friendly and can be used as coagulants to improve the performance of coagulation / filtration processes, or as adsorbents or oxidants to promote the removal of related components. The combination with other technologies can greatly improve the utilization efficiency of potassium permanganate and enhance the degradation effect of pollutants in water, but current research still has certain problems; the effect of Mn(VII) may vary depending on factors such as catalysts, reaction conditions, and pollutants. Therefore, sufficient experimental research and condition optimization are needed to obtain the best degradation effect and catalyst stability.

[0005] Permanganate and PMS are strong oxidants that can oxidize and degrade organic pollutants, but the effect of single permanganate or PMS in treating organic pollutants is not significant. Therefore, it is urgent to further improve and optimize the persulfate-based advanced oxidation technology. Summary of the invention

[0006] The purpose of the present invention is to provide a Fe(III)-g-C3N4 catalytic material and its preparation method and application, which can cooperate with permanganate to activate persulfate to treat refractory organic pollutants and has excellent oxidation catalytic degradation effect, thereby solving the problem of using reducing Fe in the existing persulfate advanced oxidation process. 2+ The activator is easy to fail, the environmental conditions for activation are high and secondary pollution of iron mud is generated. The use of electric activation technology is complex, costly and has low system efficiency.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] One of the technical solutions of the present invention is to provide a Fe(III)-g-C3N4 catalytic material, which includes a carrier g-C3N4 and a load Fe(III).

[0009] Furthermore, the carrier g-C3N4 has a smooth surface and a typical layered stacking structure.

[0010] Furthermore, the loaded substance Fe(III) is loaded on the surface and layered structure of the carrier g-C3N4.

[0011] Compared with other catalytic materials, the raw material source for preparing Fe(III)-g-C3N4 catalytic material in the present invention is abundant, cheap, and easy to produce, and the Fe(III) activator is not easy to fail and will not cause the problem of iron mud accumulation.

[0012] The second technical solution of the present invention is to provide a method for preparing the above-mentioned Fe(III)-g-C3N4 catalytic material, the steps comprising:

[0013] The iron precursor and melamine are ground and mixed, calcined, ground and then centrifuged and washed to obtain the Fe(III)-g-C3N4.

[0014] Furthermore, the iron precursor includes at least one of ferric chloride, ferric oxide and ferric sulfate.

[0015] Furthermore, the mass ratio of the iron precursor to melamine is 1:20-30.

[0016] Furthermore, the grinding and mixing time is 30 to 50 minutes.

[0017] Furthermore, the calcination temperature is 550-580° C. and the calcination time is 4-6 hours.

[0018] Furthermore, the grinding time is 30 to 50 minutes.

[0019] Furthermore, the centrifugal washing is performed three times using water, wherein the rotation speed of the centrifugal washing is 10000-11000 rpm and the time is 10-15 min.

[0020] The purpose of centrifugation washing is to remove unbound Fe 3+ With g-C3N4 impurities, Fe(III)-g-C3N4 with higher purity is obtained.

[0021] Furthermore, the method further includes drying at 80° C. after centrifugal washing.

[0022] The third technical solution of the present invention is to provide an application of the above-mentioned Fe(III)-g-C3N4 catalytic material as a catalyst in the degradation of organic matter.

[0023] The fourth technical solution of the present invention is to provide a method for degrading organic pollutants by activating PMS with Fe(III)-g-C3N4 in collaboration with Mn(VII), the steps comprising:

[0024] The above-mentioned Fe(III)-g-C3N4 and permanganate are added to the organic wastewater, mixed evenly, and then persulfate is added to react to complete the degradation of organic matter.

[0025] Furthermore, the concentration of Fe(III)-g-C3N4 in organic wastewater is 0.1 g / L.

[0026] Furthermore, the concentration of the permanganate in the organic wastewater is 20-30 μmol / L.

[0027] Furthermore, the concentration of the persulfate in the organic wastewater is 0.1 g / L.

[0028] The fifth technical solution of the present invention is to provide an application of the above method in treating organic wastewater.

[0029] The present invention discloses the following technical effects:

[0030] The Fe(III)-g-C3N4 catalytic material prepared by the present invention not only activates PMS, but also cooperates with permanganate to oxidize organic matter to produce Mn 2+ , Mn(IV) and Mn(VI) and other active species, catalyze the activation of persulfate to produce sulfate radicals, realize the secondary oxidation of organic matter, further strengthen the oxidative decomposition of PMS, improve the catalytic degradation activity, and can efficiently remove organic dyes or difficult-to-degrade organic matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0032] Figure 1 are photos of the sample before and after grinding in step S3 of Example 1, wherein a is the photo before grinding and b is the photo after grinding;

[0033] Figure 2 XRD patterns of Fe(III)-g-C3N4 prepared in Example 1 and g-C3N4 prepared in Comparative Example 1;

[0034] Figure 3 SEM images of g-C3N4 prepared in Comparative Example 1, anhydrous ferric chloride used in Example 1, and Fe(III)-g-C3N4 in Example 1, wherein a is a SEM image of g-C3N4 prepared in Comparative Example 1, b is a SEM image of anhydrous ferric chloride used in Example 1, and c is a SEM image of Fe(III)-g-C3N4 in Example 1;

[0035] Figure 4 This is the EDS spectrum of Fe(III)-g-C3N4 prepared in Example 1;

[0036] Figure 5 The degradation curves of MB with different KMnO4 dosages;

[0037] Figure 6 is the degradation rate of MB at different KMnO4 dosages;

[0038] Figure 7 is the degradation curve of methyl orange in Example 3;

[0039] Figure 8 is the degradation curve of Rhodamine B in Example 4;

[0040] Fig. 9 This is the degradation curve of methylene blue in Comparative Example 2;

[0041] Fig.10 This is the degradation curve of methyl orange in Comparative Example 3;

[0042] Fig.11 This is the degradation curve of Rhodamine B in Comparative Example 4;

[0043] Fig.12 This is the degradation curve of methylene blue in Comparative Example 5;

[0044] Fig.13 This is the degradation curve of methyl orange in Comparative Example 6;

[0045] Fig.14 This is the degradation curve of Rhodamine B in Comparative Example 7. DETAILED DESCRIPTION

[0046] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0047] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0048] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0049] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0050] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0051] Unless otherwise specified, room temperature and normal temperature referred to in the present invention refer to 25±5°C.

[0052] Example 1

[0053] Preparation of Fe(Ⅲ)-g-C3N4 catalytic material:

[0054] S1. Use an analytical balance to accurately weigh 1.0 g of anhydrous ferric chloride and 25.0 g of melamine, mix them in a mortar and grind for 40 minutes to obtain a uniform yellow powder;

[0055] S2. Transfer the yellow powder to a porcelain crucible, wrap the crucible tightly with tin foil and place it in a muffle furnace. Set the temperature of the muffle furnace to 575°C. After calcining at a constant high temperature for 4 hours, close the muffle furnace and take out the material after it cools naturally to near room temperature. Use an analytical balance to photograph, weigh and record the obtained sample.

[0056] S3. Grind the obtained sample into a fine and uniform powder using a mortar, transfer it to a centrifuge tube, add deionized water, and place it in a high-speed centrifuge for three washes at a speed of 10,000 rpm and a time of 10 min to remove the unsuccessfully bound Fe 3+ With g-C3N4 impurities, Fe(III)-g-C3N4 with higher purity is obtained;

[0057] S4. Place the washed sample in an oven set at 80°C to dry out the moisture to obtain a dry powder, grind it and store it in a bag, which is the Fe(III)-g-C3N4 catalytic material.

[0058] The photos of the samples before and after grinding in step S3 are shown in the figure below. Figure 1 As shown, a is the photo before grinding, and b is the photo after grinding.

[0059] The XRD pattern of Fe(III)-g-C3N4 in step S4 is shown in Figure 2 .

[0060] The SEM image of the anhydrous ferric chloride used in step S1 and the SEM image of Fe(III)-g-C3N4 in step S4 are shown in Figure 3 .

[0061] Figure 4 This is the EDS spectrum of Fe(III)-g-C3N4 prepared in Example 1.

[0062] Example 2

[0063] The method steps of Fe(Ⅲ)-g-C3N4 cooperating with Mn(VII) to activate PMS to degrade organic pollutants are as follows:

[0064] Deionized water was used to prepare 30 mg / L of methylene blue (MB) simulated wastewater as the target pollutant to be degraded;

[0065] S1. Prepare MB solution with a concentration of 30 mg / L using deionized water;

[0066] S2. Add the Fe(III)-g-C3N4 prepared in Example 1 to the MB solution so that the concentration of Fe(III)-g-C3N4 is 0.1 g / L, and then place it on a magnetic stirrer and stir for 1 h to evenly disperse the Fe(III)-g-C3N4 to obtain a mixed solution;

[0067] S3, take 2 mL of the mixed solution and dilute it 7.5 times with water to obtain a diluted solution as the zero-point sample, measure the absorbance at a wavelength of 662 nm, and record it as C0;

[0068] S4, adding PMS and KMnO4 to the mixed solution at the same time, and starting timing at the same time, wherein the concentration of PMS in the diluted solution is 0.1 g / L, and the concentration of potassium permanganate in the diluted solution is 10 μmol / L, 20 μmol / L, 30 μmol / L, 40 μmol / L or 50 μmol / L;

[0069] S5. During the reaction, 4 mL of sample was taken every 30 seconds and diluted 3 times. Sampling was stopped after nine samples were obtained.

[0070] S6. Filter the nine samples using a water filter with a pore size of 0.45 μm, measure the absorbance at a wavelength of 662 nm, and record the data, which is recorded as C.

[0071] The degradation curves of MB with different KMnO4 dosages are shown in Figure 2. Figure 5 As shown in Figure 2, the degradation rate of MB with different KMnO4 dosages is as follows: Figure 6 As shown. Figure 5 and Figure 6It can be seen that the MB concentration has been greatly reduced with different KMnO4 dosages. Different KMnO4 dosages have different effects on MB degradation. Among them, 30μmol / L KMnO4 has the highest degradation rate, reaching 95.4%. After further increasing the KMnO4 concentration, the MB degradation rate decreased by about 2%. Figure 5 As shown in the figure, the endpoints of MB degradation by KMnO4 at different concentrations are approximately the same, but the degradation rate of 30 μmol / L KMnO4 is the fastest within 30 s. Figure 5 From the residual ratio, it can be seen that the reaction of removing MB in this experiment mainly proceeds rapidly within 30s, and then the reaction gradually slows down. It can be seen that the activation efficiency of 0.1g / L PMS treated with 0.1g / L Fe(Ⅲ)-g-C3N4 and 30μmol / L KMnO4 is the highest, and the synergistic catalytic reaction makes the MB degradation rate reach 95.4%.

[0072] Example 3

[0073] Methyl orange degradation experiment:

[0074] The reaction conditions were room temperature and pH 7. The experiment was carried out in a glass conical flask with an effective capacity of 500 mL. The process was as follows:

[0075] S1. Mix 10 mg of methyl orange and 500 mL of water in a container to prepare a 20 mg / L methyl orange solution;

[0076] S2, add 0.2g of Fe(III)-g-C3N4 prepared in Example 1 to the methyl orange solution, place the container on a magnetic stirrer and stir for 1h, then take 4mL of the sample as the zero point sample, and measure its absorbance at a wavelength of 464nm using a spectrophotometer;

[0077] S3, add 9.4 mg of potassium permanganate and 0.2 g of PMS into the container, and start timing;

[0078] S4. During the reaction, 4 mL of sample was taken every 1 min. After the sample was filtered through a 0.45 μm filter membrane, its absorbance was measured at a wavelength of 464 nm using a spectrophotometer and the data was recorded.

[0079] The degradation curve of methyl orange is as follows Figure 7 As shown by Figure 7It can be seen that the degradation curve of methyl orange by Fe(Ⅲ)-g-C3N4 / Mn(Ⅶ) activated PMS system drops rapidly in the first 4 minutes, and the reaction proceeds rapidly at this time. The curve flattens out 4 minutes after the reaction starts but is still dropping, and the reaction rate is very slow but the reaction is still going on. After 7 minutes from the start of the reaction, the reaction reaches equilibrium, and the final degradation rate is 87.37%. The degradation effect of methyl orange by Fe(Ⅲ)-g-C3N4 / Mn(Ⅶ) activated PMS system is good.

[0080] Example 4

[0081] Rhodamine B degradation experiment:

[0082] The reaction conditions were set at room temperature and pH 7. The experiment was carried out in a glass conical flask with an effective capacity of 500 mL. The process was as follows:

[0083] S1. Mix 5 mg of rhodamine B and 500 mL of water in a container to prepare a 10 mg / L rhodamine B solution;

[0084] S2. Add 0.1 g of Fe(III)-g-C3N4 prepared in Example 1 to the rhodamine B solution, place the container on a magnetic stirrer and stir for 1 h, then take 4 mL of the sample as the zero-point sample, and measure its absorbance at a wavelength of 554 nm using a spectrophotometer;

[0085] S3, add 4.7 mg of potassium permanganate and 0.1 g of PMS into the container, and start timing;

[0086] S4. During the reaction, 4 mL of sample was taken every 3 minutes. After the sample was filtered through a 0.45 μm filter membrane, its absorbance was measured at a wavelength of 464 nm using a spectrophotometer and the data was recorded.

[0087] The degradation curve of Rhodamine B is as follows Figure 8 As shown by Figure 8 It can be seen that the degradation curve of the degradation of Rhodamine B by the Fe(Ⅲ)-g-C3N4 / Mn(Ⅶ) activated PMS system has a large slope in the first 12 minutes, and the degradation reaction rate is fast at this time. The slope of the curve decreases 12 minutes after the reaction starts. Although the reaction is still ongoing, the reaction rate is very slow. 30 minutes after the reaction starts, the degradation rate of Rhodamine B is 84%, and the degradation effect of the Fe(Ⅲ)-g-C3N4 / Mn(Ⅶ) activated PMS system on Rhodamine B is good.

[0088] Comparative Example 1

[0089] Preparation of g-C3N4:

[0090] Place melamine white powder in a porcelain crucible;

[0091] Open the muffle furnace for preheating for at least 1 hour, then put the porcelain crucible into the muffle furnace, adjust the temperature of the muffle furnace to 540℃, keep the temperature constant for 2 hours, and then let it cool down naturally. After the muffle furnace cools to room temperature, take out the sample, grind it into powder to obtain yellow g-C3N4, and dry it for storage;

[0092] The XRD pattern of g-C3N4 is shown in Figure 2 , SEM images are shown in Figure 3 .

[0093] Comparative Example 2

[0094] Compared with Example 2, the only difference is that the Fe(III)-g-C3N4 of equal mass is replaced by g-C3N4 prepared in Comparative Example 1 (KMnO4 concentration is 30 μmol / L).

[0095] The degradation curve of methylene blue is as follows Fig. 9 As shown by Fig. 9 It can be seen that in the experiment of adding g-C3N4 to catalyze PMS to degrade methylene blue, the degradation rate of methylene blue was 88.5%. Under the same reaction conditions, Fe(Ⅲ)-g-C3N4 participated in the reaction, and the degradation rate of methylene blue was 95.4%, indicating that the addition of Fe(Ⅲ) increased the degradation rate by 15%, and Fe(Ⅲ) more effectively promoted the degradation of methylene blue.

[0096] Comparative Example 3

[0097] Compared with Example 3, the only difference is that the g-C3N4 prepared in Comparative Example 1 is of equal mass to Fe(III)-g-C3N4.

[0098] The degradation curve of methyl orange is as follows Fig.10 As shown by Fig.10 It can be seen that in the experiment of adding g-C3N4 to catalyze PMS to degrade methyl orange, the degradation rate of methyl orange was 80.25%. Under the same reaction conditions, Fe(Ⅲ)-g-C3N4 participated in the reaction, and the degradation rate of methyl orange was 87.37%, indicating that the addition of Fe(Ⅲ) increased the degradation rate by 7.12%, and Fe(Ⅲ) more effectively promoted the degradation of methylene blue.

[0099] Comparative Example 4

[0100] Compared with Example 4, the only difference is that the g-C3N4 prepared in Comparative Example 1 is of equal mass to Fe(III)-g-C3N4.

[0101] The degradation curve of Rhodamine B is as follows Fig.11 As shown by Fig.11It can be seen that in the experiment of adding g-C3N4 to cooperate with permanganate to catalyze PMS to degrade rhodamine B, the degradation rate of rhodamine B was 76.2%. Under the same reaction conditions, Fe(Ⅲ)-g-C3N4 participated in the reaction, and the degradation rate of rhodamine B was 84%, indicating that the addition of Fe(Ⅲ) increased the degradation rate by 7.8%, and Fe(Ⅲ) promoted the degradation of rhodamine B more effectively.

[0102] Comparative Example 5

[0103] Compared with Example 2, the only difference is that Fe(III)-g-C3N4 is not added (the KMnO4 concentration is 30 μmol / L).

[0104] The degradation curve of methylene blue is as follows Fig.12 As shown by Fig.12 It can be seen that in the experiment of degrading methylene blue without adding Fe(Ⅲ)-g-C3N4, the degradation rate of methylene blue was 80.4%, indicating that Fe(Ⅲ)-g-C3N4 can effectively promote the degradation of methylene blue.

[0105] Comparative Example 6

[0106] Compared with Example 3, the only difference is that Fe(III)-g-C3N4 is not added.

[0107] The degradation curve of methyl orange is as follows Fig.13 As shown by Fig.13 It can be seen that in the experiment of degrading methyl orange without adding Fe(Ⅲ)-g-C3N4, the degradation rate of methyl orange was 75.3%, indicating that Fe(Ⅲ)-g-C3N4 can effectively promote the degradation of methyl orange.

[0108] Comparative Example 7

[0109] Compared with Example 4, the only difference is that Fe(III)-g-C3N4 is not added.

[0110] The degradation curve of Rhodamine B is as follows Fig.14 As shown by Fig.14 It can be seen that in the experiment of degrading rhodamine B without adding Fe(Ⅲ)-g-C3N4, the degradation rate of rhodamine B was 68.5%, indicating that Fe(Ⅲ)-g-C3N4 can effectively promote the degradation of rhodamine B.

[0111] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0112] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for degrading organic pollutants by activating PMS with Fe(III)-g-C3N4 in collaboration with Mn(VII), characterized in that the steps include: Add Fe(III)-g-C3N4 and permanganate to the organic wastewater, mix well, and then add persulfate to react, thus completing the degradation of organic matter; The Fe(III)-g-C3N4 comprises a carrier g-C3N4 and a load Fe(III); the carrier g-C3N4 has a smooth surface and a layered stacking structure; the load Fe(III) is loaded on the surface of the carrier g-C3N4 and in the layered stacking structure; The preparation steps of the Fe(III)-g-C3N4 include: grinding and mixing an iron precursor and melamine, calcining, grinding, centrifuging and washing, and drying at 80° C. to obtain the Fe(III)-g-C3N4; The mass ratio of the iron precursor to melamine is 1:20-30; the grinding and mixing time is 30-50 minutes; the iron precursor includes at least one of ferric chloride, ferric oxide and ferric sulfate; The calcination temperature is 550-580°C and the time is 4-6 hours; the grinding time is 30-50 minutes; the centrifugal washing is three times of centrifugal washing with water at a speed of 10000-11000 rpm and a time of 10-15 minutes; The concentration of Fe(III)-g-C3N4 in organic wastewater is 0.1 g / L; the concentration of permanganate in organic wastewater is 10-30 μmol / L; and the concentration of persulfate in organic wastewater is 0.1 g / L.

Citation Information

Patent Citations

  • Porous metal (iron, nickel and cobalt) doped graphite phase carbon nitride photocatalyst as well as preparation method and application thereof

    CN114797942A

  • Preparation method and application of magnetic multivalent iron-manganese oxide catalyst

    CN115555027A